Developing Cross Cultural Competence in Adult Learning in the ASEAN Context - Panahon, Atanacio, II (Archīum Ateneo, 2015)
The rise of the borderless world and networked organizations, as well as the almost irreversible phenomenon of increased movement of workers, students, visitors, and retirees to overseas destinations, has made cross-cultural competence a compelling proposition. A review of researches on cross-cultural competence points to a limited discussion on this topic in the context of adult and lifelong learning in the Asia and Pacific region. In the past 30 years, there has been a general push among higher education institutions (HEIs) in Europe, North America, and some parts of Asia, especially among business schools, to structure teaching, research, and service activities to international level. Toward this end, the capability of the faculty of HEIs in handling cultural diversity in the classroom is being addressed through formal training and faculty exchange. Admittedly, however, the issue of cross-cultural competence among teachers in adult education, particularly in the fields of continuing education and vocational training in Southeast Asia, remains a big challenge. This paper clarifies the definition of cross-cultural competence in the context of adult learning and discusses the essential elements of cultural competence. The relationship of cross-cultural competence to the new construct called cultural intelligence, or CQ, is likewise discussed. The paper also outlines the reasons that require teachers in adult education to be culturally competent themselves. One reason expounded in the paper is that teachers who are culturally savvy are more capable and effective in facilitating the learning process of adults to handle cultural conflicts. The importance of being culturally competent also highlights the role of technical and vocational education and training (TVET) in equipping would-be workers for overseas posting with the knowledge and skills to handle cross-cultural dynamics. In Southeast Asia, TVET is part of adult learning, and, in this regard, this paper suggests that the training component should include learning modules on tackling a multicultural environment.